Does liver density change in computed tomography in COVID-19 patients? - Bozdağ, Ahmet; Bozdag, Pinar Gundogan; Karlıdag, Gulden Eser; Kalaycı, Mehmet (My University, 2022)
Aim: Corona virus disease 2019 (COVID-19) mainly affects the lungs. However, other organs are affected as well. This article aimed to evaluate the effects of coronavirus infection on liver density in addition to the laboratory findings. Materials and Methods: Biochemical parameters and non-contrast tomography images of the patients who presented to the pandemic clinic were studied retrospectively. Densities of the right and left lobes of the liver were measured. Patients were divided into two groups according to the results of polymerase chain reaction (PCR) tests. Results: Our study included 117 PCR (+) and 66 PCR (-) patients. Statistical comparison of the two groups revealed a significant difference in age, densities of the right and left lobes of the liver, and aspartate aminotransferase, gammaglutamyl transferase, total bilirubin, and lactate dehydrogenase values (p < 0.05). According to the correlation test, there was a negative correlation between the densities of the right and left lobes of the liver and transaminases. Conclusion: An inverse relationship emerged between liver density and transaminases. Therefore, liver functions should be monitored more closely in COVID-19 patients during treatment, and if it is at high levels, treatment should be started early.
Keywords: Genel ve Dahili Tıp; Patoloji; Mikrobiyoloji